The impact of mathematical disposition and self-efficacy beliefs on secondary school students' mathematical literacy - Nurhayati, Hanifah; Hasanah, Aan; Dasari, Dadan (Jurnal Elemen, 2025)
The mathematical literacy skills of Indonesian students, as reflected in the PISA results, continue to be a concern because of their poor performance. Students with high mathematical disposition and high self-efficacy are often more proficient in mathematical literacy. This study aimed to examine how mathematical disposition and self-efficacy affect students’ mathematical literacy skills. This study employed a quantitative approach with a nonexperimental design and adopted a causal associative methodology. Data collection involved administering mathematical disposition and self-efficacy questionnaires, along with a mathematical literacy test, to 56 junior high school students. The analysis was performed using structural equation modeling-partial least squares (SEM-PLS) in the JASP 0.18.3.0 application. The results showed that mathematical disposition significantly enhances both self-efficacy and mathematical literacy skills. Conversely, while self-efficacy positively influenced mathematical literacy skills, the effect was not statistically significant.